Activation of adiponectin receptors has negative impact on muscle mass in C2C12 myotubes and fast-type mouse skeletal muscle. - Rika Ito; Masaki Higa; Ayumi Goto; Megumi Aoshima; Akihiro Ikuta; Kazuya Ohashi; Shingo Yokoyama; Yoshitaka Ohno; Tatsuro Egawa; Hirofumi Miyata; Katsumasa Goto (PLoS ONE, 2018)
This study investigated the effects of AdipoRon, which is an agonist for adiponectin receptor 1 (AdipoR1) and AdipoR2, on the protein content, myotube diameter, and number of nuclei per myotube of C2C12 cells and skeletal muscle mass in C57BL/6J mice. AdipoRon suppressed the protein content, myotube diameter, and number of nuclei per myotube of C2C12 cells of C2C12 myotubes in a dose-dependent manner. Adiponectin-associated decline of protein content, diameter, and number of nuclei per myotube in C2C12 myotubes was partially rescued by knockdown of AdipoR1 and/or AdipoR2. Phosphorylation level of AMPK showed a trend to be increased by AdipoRon. A significant increase in phosphorylation level of AMPK was observed at 20 μM AdipoRon. Knockdown of AdipoR1 and/or AdipoR2 rescued AdipoRon-associated decrease in protein content of C2C12 myotubes. AdipoRon-associated increase in phosphorylation level of AMPK in C2C12 myotubes was suppressed by knockdown of AdipoR1 and/or AdipoR2. Successive intravenous injections of AdipoRon into mice caused a decrease in the wet weight of plantaris muscle (PLA), but not in soleus muscle (SOL). Mean fiber cross-sectional area of PLA, but not of SOL, was significantly decreased by AdipoRon administration. On the one hand, the expression level of phosphorylated AMPK and ubiquitinated protein in SOL and PLA muscles was upregulated by AdipoRon administration. On the other hand, AdipoRon administration induced no changes in the expression level of puromycin-labeled proteins in both SOL and PLA muscles. Expression level of adiponectin in extensor digitorum longus (EDL) muscle was increased by aging, but not in SOL muscle. Aging had no effect on the expression level of AdipoR1 and AdipoR2 in both muscles. Phosphorylation level of AMPK in EDL was increased by aging, but not SOL muscle. Results from this study suggest that high level of circulating adiponectin may induce skeletal muscle atrophy, especially fast-type muscle.